2018
DOI: 10.29226/tr1001.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Money Supply on Some Macroeconomic Variables on The Nigerian Economy

Abstract: The link between aggregate money supply, inflation and economic growth has raised a lot of scholarly debate in the field of economics and finance. The study sets to investigate the impact of money supply on macroeconomic variables in Nigeria from 1985 to 2016. The specific objectives of the paper were to ascertain the impact of narrow money supply, broad money supply, inflation rate, and exchange rate on real gross domestic product on one hand, and narrow money supply, broad money supply and exchange rate on c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 4 publications
1
5
0
Order By: Relevance
“…This confirms significant relationships between GDP growth rate, inflation rate, exchange rate with USD, deposit rate, and lending rate with money supply.Our findings indicate a significant relationship between money supply and GDP growth rate (RGDP), in agreement withGeorge et al (2018). This aligns with the negative correlation observed in previous research byIfionu and Akinpelumi (2015).…”
supporting
confidence: 92%
“…This confirms significant relationships between GDP growth rate, inflation rate, exchange rate with USD, deposit rate, and lending rate with money supply.Our findings indicate a significant relationship between money supply and GDP growth rate (RGDP), in agreement withGeorge et al (2018). This aligns with the negative correlation observed in previous research byIfionu and Akinpelumi (2015).…”
supporting
confidence: 92%
“…Various studies support the impact of these factors (see Karahan, 2020;Antwi et al, 2020;Fatbardha, 2020;Koirala, 2018;Achouak et al, 2018;Rasaqque et al, 2017;Fassil, 2017;Eze & Atuma, 2017;Ingebire et al, 2020;Abdul et al, 2018;Hussain & Zafar, 2018;Ditim et al, 2018;Diemante et al, 2020;Onakoya et al, 2019;Hicham, 2018;George et al, 2018;Adeyemi et al, 2020;Ezeaku et al, 2018;Anoke et al, 2016;Sushil, 2020;Abille & Mpure, 2020;Cambodia et al, 2018;Ibi et al, 2019;Owolabi & Adegbite, 2014). Therefore, this study examines the impact of trade balance, exchange rate, and money supply on economic growth, focusing on Nigeria's economy, and aims to provide policy recommendations for other African countries.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The research confirmed the long-term link between monetary variables and economic growth. George (2018), based on research conducted for the period from 1985 to 2016 on the example of Nigeria, concludes that inflation has an inverse effect on economic growth. Sequeira (2021) confirms that inflation has a negative impact on economic growth.…”
Section: Empirical Researchmentioning
confidence: 99%